Changing ceramic traditions at Agila ancestral village, Hood Bay, Papua New Guinea. Issue 2 (4th May 2018) - Skelly, Robert; David, Bruno; Leavesley, Matthew; Petchey, Fiona; Guise, Alu; Tsang, Roxanne; Mialanes, Jerome; Richards, Thomas
Abstract: Accounts of New Guinea's recent past are replete with both archaeological and ethnographic evidence of trade that indirectly connect virtually the entire country from coast to highland. One consequence has been a bias towards central places (e.g. Mailu Island) and/or large-scale production villages (e.g. of the Port Moresby region) as origin locations for distributed goods. Inversely, there has also been attention paid to distant, recipient points in the landscape (e.g. Gulf of Papua lowlands) where incoming traders turn back home to their originating villages. Less attention has been given to those extreme edges where separate networks indirectly connect. Here we present new evidence from Hood Bay on the south coast of PNG, a region that lies at a crossroads between the west-sailing Motu hiri and eastern Mailu Island ceramicists and seafaring traders. By being on the margins of each, Hood Bay is geographically well positioned to investigate changing inter-regional seafaring networks along a broad coastal expanse. We present initial results from excavations at the Agila village site, Hood Bay, where a changing incidence of western Motu and Mailu ceramics is evident. The results signal that Hood Bay villagers reorganised alliances and access to commodities and influence, depending on the prevailing conditions beyond their immediate western and eastern horizons.